Effect of the Murraya koenigii and Moringa oleifera Leaf Extracts on the Ovarian Follicular Population and other Organ Weights in Rats (Rattus norvegicus) - Bogapathi, Sampath K.; Shetty, Ramesh H. S.; Sumanta, Nandi; Venkataswamy, Girish K. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The object of the present study was to evaluate the effect of Murraya Koenigii and Moringa Oleifera plant leaf extracts on ovarian follicular population, body weight and other organ weights in the rats. A total of 42 rats with a mean body weight of 160.05 gms were divided in 7 groups with six rats in each. Group 1, which served as control rats, was administered with 0.5 ml vehicle. Group II,III and IV were administered Murraya Koenigii leaves extract at 100,300 and 1000 mg/kg/b.w. Group V, VI, and VII were administered Moringa Oleifera at 100,300 and 1000 mg/kg/b.w, respectively. The mean ± SE values of a number of surface ovarian follicles, small antral follicles, and overall preantral follicles were significantly higher in the Group IV, VI, and VII as compared to the control group that received Murraya koenigii at 1000 mg/kg/b.w and Moringa Oleifera at 300 mg/kg.b.w. and 1000 mg/kg.b.w. The mean ovarian weight was significantly higher in the Group IV and Group VI and VII groups compared to the control group.